2021
DOI: 10.3389/fcvm.2021.747497
|View full text |Cite|
|
Sign up to set email alerts
|

Extracorporeal Cardiac Shock Waves Therapy Improves the Function of Endothelial Progenitor Cells After Hypoxia Injury via Activating PI3K/Akt/eNOS Signal Pathway

Abstract: Background: Extracorporeal cardiac shock waves (ECSW) have great potential in the treatment of coronary heart disease. Endothelial progenitor cells (EPCs) are a class of pluripotent progenitor cells derived from bone marrow or peripheral blood, which have the capacity to migrate to ischemic myocardium and differentiate into mature endothelial cells and play an important role in neovascularization and endothelial repair. In this study, we investigated whether ECSW therapy can improve EPCs dysfunction and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The focal pressure can reach 3~75 MPa, the frequency of the SW is 0.1~0.2 MHz, and the energy flow density is 0.005~0.640 mJ/mm 2 , which is only 1/10 of the extracorporeal lithotripsy energy. 16 The sulfur hexafluoride MB consists of a sulfur hexafluoride gas core and an external phospholipid shell, with a diameter of about 2.5 μm. 17 Sulfur hexafluoride MB can display 2 states in the application process, stable cavitation, and inertial cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…The focal pressure can reach 3~75 MPa, the frequency of the SW is 0.1~0.2 MHz, and the energy flow density is 0.005~0.640 mJ/mm 2 , which is only 1/10 of the extracorporeal lithotripsy energy. 16 The sulfur hexafluoride MB consists of a sulfur hexafluoride gas core and an external phospholipid shell, with a diameter of about 2.5 μm. 17 Sulfur hexafluoride MB can display 2 states in the application process, stable cavitation, and inertial cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies confirmed that the cardioprotective effects of Vitro cardiac shock therapy are primarily achieved by promoting the proliferation, mobilization, and activation of endothelial progenitor cells [26]. Subsequent studies further found that ECSW treatment (500 injections at 0.09 mJ/mm2) significantly improved cell viability, anti-apoptosis, migration, and tube formation of EPCs, which may be related to the promotion of downstream p-eNOS and anti-apoptotic protein Bcl-2 expression and inhibition of pro-apoptotic protein Bax and Cas-pase3 expression through PI3K/AKT and MEK/ERK signaling pathways [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway is an important pathway by which ginsenosides improve apoptosis. The activation of this pathway promotes angiogenesis, alleviates tissue hypoxia, suppresses cell damage, and improves MC apoptosis ( Wang M. et al, 2021 ; Zhang J. et al, 2021 ; Cao et al, 2021 ). Evidence showed that ginsenoside Rb1, Rb3, Rb2/Rb3 combination, Rd, Rg1, Rg2, Rg3, Rh1, Rh2, Rk3 activated the PI3K/Akt-mediated signaling pathway ( Supplementary Table S1 ).…”
Section: Effects and Mechanisms Of Ginsenosides On Myocardial Cell Ap...mentioning
confidence: 99%